Impact of Social Networking Sites on Students’ Learning English Language at Tertiary Level in Bangladesh - Chowdhury, A.K.M. Iftekharul Alam (Studies in ELT and Applied Linguistics, 2021)
With the advancement in technology, Social Networking Sites (SNS) are being used by millions of students in Bangladesh for various purposes. People use SNS for communication, interaction' sharing posts, photos, videos; creating blogs, sending messages, and for real time conversations (Zaidieh, 2012). Students can learn their target language through SNSs as these platforms engage students more and inspire them. Moreover, the usage of SNSs minimises learners’ fear and nervousness and authority of the instructor (Gilbert, Fiske, & Lindzey, 1998; Beauvois, 1998, cited in Millis, 2011). Moreover, an opportunity of interaction for both teachers and students is ensured through authentic tasks and materials which promote constructivist learning through meaningful communication (Woo, Herrington, Agostinho, & Reeves, 2007). This study has explored the impact of SNS in learning English at tertiary level. So, it focuses on the effects of Social Networking Sites in language learning platform, developing reading, writing, listening and speaking skills and creating ease to teachers and learners in English has been examined in this study. To investigate this, I implemented quantitative research method with 120 students studying Honour’s in English Language and Literature at Public, National and Private Universities. Forty students were selected randomly from each of the university category. All the students were surveyed by using close-ended questionnaire and later descriptive statistical method was used to analyse the data. Despite having hesitation of communicating with each other, it is clearly evident that students use SNS mainly Facebook to improve their language skills.